Associations of Gla-rich protein and interleukin-1β with coronary artery calcification risk in patients with suspected coronary artery disease - Zengwei, Cheng; Shiyi, Gao; Pinfang, Kang; Dasheng, Gao; Jun, Wang; Sigan, Hu (Frontiers in Endocrinology, 2025)
BackgroundGla-rich protein (GRP) and interleukin-1β (IL-1β) are recognized as reliable biomarkers for evaluating inflammation and are effective predictors of cardiovascular disease. However, the relationship between GRP, IL-1β, and coronary artery calcification (CAC) in patients with suspected coronary artery disease (CAD) remains unclear. Therefore, we investigated the association between these inflammatory biomarkers (GRP and IL-1β) and CAC in patients with suspected CAD.MethodsThis prospective study included patients with suspected CAD who underwent coronary computed tomography angiography (CTA). Fasting venous blood samples were collected at admission, and GRP and IL-1β levels were quantified using enzyme-linked immunosorbent assays (ELISA). The Agatston score was calculated to assess coronary artery calcification (CAC) based on coronary CTA findings.ResultsA total of 120 patients were included in this study. Multivariate logistic regression analysis revealed that GRP [odds ratio (OR), 1.202; 95% confidence interval (CI), 1.065-1.356; p = 0.003] and IL-1β (OR, 1.011; 95% CI, 1.002-1.020; p = 0.015) were independent risk factors for CAC severity. Receiver operating characteristic (ROC) curve analysis demonstrated that GRP had a predictive ability for CAC, with an area under the curve (AUC) of 0.830 [95% CI (0.755, 0.904)]. IL-1β exhibited an AUC of 0.753 [95% CI (0.660, 0.847)]. The combination of GRP and IL-1β in a predictive model improved the AUC to 0.835. Additionally, GRP and IL-1β levels showed a strong positive correlation (r = 0.6861, p < 0.05), and GRP was significantly associated with CAC severity (r = 0.5018, p < 0.05).ConclusionsElevated levels of GRP and IL-1β, as inflammatory biomarkers, were associated with CAC in patients with suspected CAD. These biomarkers may provide valuable insights into the pathophysiology of coronary artery calcification and contribute to improved risk stratification in this patient population.